CMET-16. THE ROLE OF SURGICAL RESECTION OF MELANOMA BRAIN METASTASES IN THE IMMUNOTHERAPY ERA. (5th November 2018) - Alvarez-Breckenridge, Christopher; Giobbie-Hurder, Anita; Gill, Corey; Bertalan, Mia; Stocking, Jackson; Kaplan, Alexander; Nayyar, Naema; Lawrence, Donald; Flaherty, Keith; Shih, Helen; Oh, Kevin; Batchelor, Tracy; et al.
Abstract: Immune checkpoint blockade has systemic efficacy in patients with metastatic melanoma, including those with brain metastases. However, immunotherapy-induced intracranial tumoral inflammation can lead to neurologic compromise, requiring steroids, which abrogate the systemic efficacy of this approach. We hypothesize that early surgical intervention creates an opportunity for improved survival amongst patients undergoing immune checkpoint blockade for metastatic melanoma. An IRB approved, single institution retrospective study identified 142 patients with melanoma brain metastases treated with immune checkpoint blockade. Overall survival was calculated from date of diagnosis of brain metastasis until death from any cause. Model building included a prognostic model of overall survival and the effect of sequencing of immunotherapy and surgery on overall survival. The 2-year overall survival for patients treated with CTLA-4, PD-1 or combinatorial blockade were 19%, 54%, and 57%, respectively. Patients undergoing surgery for melanoma brain metastases prior to immunotherapy had a median survival of 22.7 months (95% CI: 12.6 to 39.2) compared to 9.3 months (95% CI: 5.7 to 31.1) for patients undergoing surgery after immunotherapy ( P =0.06). Amongst surgical patients, the sequence of immunotherapy, diagnosis of brain metastases, and surgery was significantly associated with the hazard of death ( P =0.002). Surgery for treatment-naïve intracranial disease followed by immunotherapy is associated with increased overall survival compared to patients who underwent surgery for brain metastases that developed on immunotherapy (HR: 2.96, 95% CI: 1.4 to 6.1). These results suggest that in treatment-naïve patients, early surgical resection for local control should be considered prior to commencing immunotherapy.